2021
DOI: 10.36740/wlek202104123
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection After Cesarean Section in Ukraine: Results a Multicenter Study

Abstract: The aim: To obtain the first national estimates of the current prevalence rate of SSI after CSEC and antimicrobial resistance of causing pathogens in Ukraine. Materials and methods: We performed a retrospective multhicentre cogort study based surveillance data was conducted from May 2017 to December 2019. The study population consisted of all women who had a cesarean section in 11 regional women hospitals of Ukraine. Definitions of SSI after cesarean section were used from the CDC/ NHSN. Results: A total of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
1
14
3
3
Order By: Relevance
“…In that study, the overall proportion of ESBL production among Enterobacteriaceae was 18.3% [27]. However, our results are quite contrary to a study done in Tanzania that described merely 2 (13%) of the enteric GNB as ESBL producers [29].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In that study, the overall proportion of ESBL production among Enterobacteriaceae was 18.3% [27]. However, our results are quite contrary to a study done in Tanzania that described merely 2 (13%) of the enteric GNB as ESBL producers [29].…”
Section: Discussioncontrasting
confidence: 99%
“…This nding is similar to the well-documented data found in the literature showing a preponderance of mono-bacterial infections in wound infections [24]. However, in a recent study done in Ukraine, 56.1% (192/342) reported that postcaesarean wound infections are bi-bacterial [27]. Regarding bi-bacterial infections, the most common agents involved are P. aeruginosa and S. aureus (42.9%) (12 out of 28 cases), warranting effective combination drugs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The global range of SSI is very wide. This study observed prevalence of SSI was 14.7% compared to many other studies like Jasim et al, 11 Nikita Dhote et al, 12 Aidyn G. Salmanov et al, 13 discordance to our study Meo et al, 14 , Ketcheson F et al, 15 Moulton LJ et al 16 and Noronha et al 17 observed very low (1.9% to 6.9%) prevalence of SSI and De Nardo P et al 18 found very high 48% prevalence of SSI. The difference of SSI prevalence could be due to different study samples, use of antibiotics, preexisting disease, data used for analysis.…”
Section: Discussioncontrasting
confidence: 40%